Major Aorto Pulmonary Collateral Arteries (MAPCA) with Tetralogy of Fallot and Pulmonary Artesia in Middle Age Adult: a Rare Finding - Sunita Gupta; Sanjeev Gupta; Tanuj Mehta (Acta Medica Indonesiana, 2015)
A forty four years old male patient presented with headache and dizziness in our outpatient department. On examination, he had pulse rate of 96 /min, blood pressure of 122/80 mmHg, JVP was not raised. He had clubbing and cyanosis on General physical examination. On auscultation pansystolic murmur was heard all over the chest. His respiratory and abdominal examination was normal. There were no significant findings on electrocardiography and skiagram chest. Echocardiography revealed ventricular septal defect with overriding of aorta, pulmonary artery could not be visualised. On computrized tomography pulmonary angiography revealed Ventricular septal defect with overriding of aorta. The main and  normally confluent right and left pulmonary arteries were not visualized